Case of Cytomegalovirus Colitis in a Patient with Type 2 Diabetes Mellitus - Gupta, Ankur; Jain, Priyanka (Journal of Digestive Endoscopy, 2017)
Cytomegalovirus (CMV) colitis usually affects immunocompromised hosts. We report a patient with type 2 diabetes mellitus who presented with massive lower gastrointestinal bleed due to CMV colitis, which proved to be fatal. Awareness about this life-threatening entity is important in patients who have impaired immune response.
Keywords: Cytomegalovirus; gastrointestinal bleed; immunity